The Last American Puritan : the Life of Increase Mather, 1639-1723. - Hall, Michael G. (Michael Garibaldi) (Wesleyan University Press, 2011)
A critically acclaimed and accessible biography of one of the towering figures of New England's colonial period; winner of The Conference on Christianity and Literature's Book Award.